PENINGKATKAN KETERAMPILAN MEMBACA AKSARA JAWA MENGGUNAKAN PERMAINAN SCRABBLE BERBANTUAN KARTU HANACARAKA - Tri Hastuti (Jurnal Pendidikan Nusantara, 2022)
The formulation of the problem in this research is how the learning process, how much improvement in Javanese script reading skills, and changes in student behavior using card games with Javanese letter card media in fourth grade students of SDN Keputran 04. This CAR was carried out in two cycles. There was a change in learning behavior from the aspects of attention, response, responsibility, the way students responded and the students' activities in journaling. The values of cooperative, orderly, critical, and confident character look good. Pre-cycle results 5 (28%) of students completed and 13 (72%) did not complete. The class average is 64.4. Cycle 1 class average 68.3, Cycle 2 class average 81.94.